Economic Law as an Economic Good : Its Rule Function and its Tool Function in the Competition of Systems. - Meessen, Karl M.; Bungenberg, Marc; Puttler, Adelheid (Sellier. European Law Publishers, 2009)
Governments, or at least the clever ones among them, are aware of the factors guiding business activities. In the course of adopting and enforcing economic legislation, they seek to attract business activities in order to increase national income (and fiscal revenues), generate employment opportunities and, very generally, please voters. Hence economic law may be considered an economic good, as suggested by the title of this book. That function, which most rules of economic law have in the competition of systems, was strengthened by the worldwide liberalization of trade. Today, it is of greater significance than ever before. Lawyers and economists, academics and practitioners from inside and outside Germany have taken a look at the facts and discussed approaches to conceptualizing them. The resulting thirty essays collected in this volume contribute to the interpretation of existing, and the making of new, economic law.